Repositioning microbial biotechnology against COVID‐19: the case of microbial production of flavonoids. Issue 1 (13th October 2020) - Goris, Tobias; Pérez‐Valero, Álvaro; Martínez, Igor; Yi, Dong; Fernández‐Calleja, Luis; San León, David; Bornscheuer, Uwe T.; Magadán‐Corpas, Patricia; Lombó, Felipe; Nogales, Juan
Summary: Coronavirus‐related disease 2019 (COVID‐19) became a pandemic in February 2020, and worldwide researchers try to tackle the disease with approved drugs of all kinds, or to develop novel compounds inhibiting viral spreading. Flavonoids, already investigated as antivirals in general, also might bear activities specific for the viral agent causing COVID‐19, SARS‐CoV‐2. Microbial biotechnology and especially synthetic biology may help to produce flavonoids, which are exclusive plant secondary metabolites, at a larger scale or indeed to find novel pharmaceutically active flavonoids. Here, we review the state of the art in (i) antiviral activity of flavonoids specific for coronaviruses and (ii) results derived from computational studies, mostly docking studies mainly inhibiting specific coronaviral proteins such as the 3CL (main) protease, the spike protein or the RNA‐dependent RNA polymerase. In the end, we strive towards a synthetic biology pipeline making the fast and tailored production of valuable antiviral flavonoids possible by applying the last concepts of division of labour through co‐cultivation/microbial community approaches to the DBTL (Design, Build, Test, Learn) principle. Abstract : Coronavirus‐related disease 2019 (COVID‐19) became a pandemic in February 2020 and worldwide researchers try to tackle the disease with approved drugs of all kinds, or to develop novel compounds inhibiting viral spreading. Flavonoids, already investigated as antivirals in general, also might bear activities specific for the viral agent causing COVID‐19, SARS‐CoV‐2. Microbial biotechnology and especially synthetic biology may help to produce novel flavonoids with antiviral activity.